Analisis Sitem Pengendalian Internal Pada Kas Badan Perencanaan Pembangunan Penelitian Dan Pengembangan Daerah (Bappelitbangda) Kab.Sukabumi - Marsela Marsela; Acep Suherman (AKUNTANSI 45, 2024)
This study aims to find out how the Analysis of Internal Control System in the Treasury of the Regional Developmen Planning, Research and Developmen Agency (Bappelitbangda) Kab.Sukabumi. This research focuses on the internal control system for cash because there is often misuse of agency assets. Therefore researchers are interested in conducting research on Intrenal Control System Analysis on Cash. The method used in this study is a qualitative method. Data collection techniques used are interviews, observation and documentation. The data analysis technique used in this study is by: (1) Collecting data to obtain the desired information. (2) Reducing data or summarizing the main things. (3) Presenting data to draw conclusions. (4) Summing up the results of the research The results of the research show Research and Development Agency (Bappelitbangda) Kab.Sukabumi is good and is in accordance with the system contained in PP No. 60 of 2008.